2021
DOI: 10.1021/acs.langmuir.1c00785
|View full text |Cite
|
Sign up to set email alerts
|

Emission Color Tuning and White Light Generation from a Trimolecular Cocktail in Cationic Micellar System with Promising Applicability in the Anticounterfeiting Technology

Abstract: The development of photoluminescent (PL) systems, displaying multiple stimuli-responsive emission color tuning, has been the pressing priority in the recent times due to their huge role in contemporary lighting and anticounterfeiting technologies. Acknowledging this importance, we present a simple and eco-friendly PL system showing emission color tuning in response to different stimuli, that is, the composition of the system, pH, excitation wavelength, and the temperature with the plus point of getting signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“… a Measured in THF/H 2 O solvent (at f w = 60%). b Obtained from DLS results. c Determined from TRPL profiles at λ ex = 365 nm and λ em = 405 nm. d Calculated from the equation: E F R E T = 1 τ D A τ D . e Energy transfer efficiency ( E ET ) of Mixture : E = 5% (without FRET process). f Energy transfer efficiencies ( E ET ) of M and [ c 2 ]A : combined energy transfers of PET and FRET. g Calculated from the equation: Φ s = Φ r ( A r F s / A s F r )( n s 2 / n r 2 ). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Measured in THF/H 2 O solvent (at f w = 60%). b Obtained from DLS results. c Determined from TRPL profiles at λ ex = 365 nm and λ em = 405 nm. d Calculated from the equation: E F R E T = 1 τ D A τ D . e Energy transfer efficiency ( E ET ) of Mixture : E = 5% (without FRET process). f Energy transfer efficiencies ( E ET ) of M and [ c 2 ]A : combined energy transfers of PET and FRET. g Calculated from the equation: Φ s = Φ r ( A r F s / A s F r )( n s 2 / n r 2 ). …”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence quantum yields (Φ) were obtained using the following equation: Φ s = Φ r false( italicA normalr italicF normals / italicA normals italicF normalr false) false( italicn normals 2 / italicn normalr 2 false) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of high-security anticounterfeiting technologies based on photoluminescent, photochromic, and hydrochromic materials is a significant research area in recent years and has showed rapid growth for reported intelligent systems such as stimuli-responsive inks, labels, and security tags. In today’s world, governments, companies, and customers look for the most efficient anticounterfeiting technology with high security, intelligent and multi-level authentication, and complex or high-tech formulation to increase the security of confidential documents such as banknotes, passports, national cards, certificates, and valuable products (drugs, vaccines, chemicals, and other materials or instruments related to human health). , The encryption and encoding of information as security tags such as quick responsive (QR) codes and barcodes is a significant solution to overcome counterfeiting and copying of confidential and security documents. However, scientists are interested in developing a new category of anticounterfeiting materials for the printing of security tags with multi-level security and a complex authentication process.…”
Section: Introductionmentioning
confidence: 99%